Apakah Kesenangan dan Romantisme Menimbulkan Cinta Merek? - Pingki Dwi Aprilianingsih; Harmanda Berima Putra (Jurnal Bisnis dan Ekonomi, 2021)
This study aims to examine Customer Delight, romanticism towards brand love of body care products. This study uses quantitative methods. The sample in this study were users of body care products in the city of Semarang. Data was collected using an online questionnaire through a goggle form which was distributed to 150 respondents for one month. Data analysis used regression analysis from SPSS. The results show that Customer Delight, romanticism has a positive effect on brand love of body care products.